Designing disease-resistant crops: From basic knowledge to biotechnology - Selena Giménez-Ibánez (Mètode Science Studies Journal: Annual Review)
Ancient records describe how plant diseases were attributed to many causes, including divine power, religious belief, and superstition. Far from these days, we now have detailed knowledge about how plant immunity is executed. Plants employ two types of sensors to perceive and defeat the litany of pathogenic organisms that attack them, whilst microbes deploy a myriad of specialized weapons to suppress immunity and promote infection. This opens a path to exploiting these insights to increase crop resistance. Here we describe novel biotechnological approaches for designing superior disease-resistant crops to fight agricultural losses in the field while reducing chemical inputs, towards a more sustainable agriculture that ensures food security.